Strategic minerals exploration in the central andes: sustainable sources of raw materials for green technologies - Benites Negrón, Diego (2021)
Securing a sustainable supply of critical raw materials such as In, Ge, and Ga has become a global concern in recent years. These elements are essential for the manufacture of modern digital and green technologies. The central-Andean metallogenetic belts in Peru bear potential for strategic metal/metalloid resources in some of the great variety of magmatic-hydrothermal and other hydrothermal mineral deposits they host. This doctoral thesis aims to provide a detailed survey on the ore mineralogy and mineral geochemistry at different metalliferous districts in the Central Andes of Peru, including constraints on the temporal and spatial distributions of trace elements with particular focus on In, Ge, and Ga. This contribution also expects a better understanding regarding the geochemical behavior of In, Ge, and Ga during magmatic-hydrothermal and other hydrothermal processes, as well as the metallogenetic preference of each of these elements, contributing to the development of exploration guidelines. In general, the highest In, Ge, and Ga contents are found in sphalerite. Amongst analyzed samples, sphalerite is particularly rich in In in low-sulfidation assemblages in Cordilleran mineralization (up to 1.7 wt.% in Ayawilca); however, in the Morococha district, the highest In values are found in sphalerite from high-sulfidation assemblages (up to 1456 ppm), followed by sphalerite from low-sulfidation assemblages (up to 459 ppm in the Manto Italia body), whereas in intermediate-sulfidation assemblages its content is highly variable. The highest Ga contents are recorded in sphalerite from epithermal veins overprinting the Toromocho porphyry (up to 1739 ppm). Sphalerite from MVT deposits is remarkably Ge-rich, with values up to 1861 ppm in the San Vicente deposit. Chalcopyrite (up to 1185 ppm In in the Ayawilca deposit) and stannite (up to 1908 ppm in the Ayawilca deposit) can also host significant In contents. Tetrahedrite-tennantite samples from intermediate-sulfidation assemblages in the Morococha district occasionally host significant Ge contents (up to 266 ppm); however, values are in general low. In analyzed galena In, Ge, and Ga contents are mostly at the sub-ppm level. In sphalerite, In, Ge, and Ga are incorporated into the crystal lattice via coupled substitutions. Substitution schemes for the incorporation of In, Ge, and Ga in the other analyzed ore minerals remain unclear. Some spatial and temporal trends in In, Ge, and Ga contents, mostly in sphalerite, have been observed. In intermediate-sulfidation assemblages from the Morococha district, sphalerite shows continuous In and Cu depletion from proximal-to-porphyry Cu metalliferous zone to distal-to-porphyry Ag-Pb metalliferous zone, and within single sampled orebodies, sphalerite records In depletion and Ge enrichment from early to late generations. These observations have led to the conclusion that in porphyry-related polymetallic mineralization, the distribution of In in sphalerite is controlled by i) sourcing of In via metal-rich magmatic-hydrothermal fluids; ii) a relatively high availability of Cu in the mineral system; iii) a relatively high temperature of the mineralizing fluid (> 250ºC) or low pH favoring the stability Cl complexes, and iv) availability of Cl to form In (and Cu) chloride complexes. Chalcopyrite from intermediate-sulfidation assemblages in the Morococha district shows a trend toward Se and Hg depletion and Sn and Ag enrichment from proximal to distal orebodies. As for VMS deposits, in the Sofía-D zone-refined massive sulfide body in the María Teresa deposit, there is a progressive enrichment in In, Cu, Mn, and Se and a depletion in Ge in sphalerite towards the chalcopyrite-rich basal domain. Finally, in the San Vicente and Shallipayco MVT deposits, Ge-richest sphalerite, which shows bright orange and yellow colors, crystalized relatively late in the respective paragenetic sequences.